PENGARUH KOMITE AUDIT TERHADAP KUALITAS LABA - SUARYANA, AGUNG (Jurnal Ilmiah Akuntansi dan Bisnis, 2007)
This research aims at examining the impact of audit committees on earnings quality. The study is motivated by the controversy of previous studies about performance of audit committee. Earnings quality is measured by Earnings Responsse Coefficient (ERC). Sample of the study consists of 97 manufacturing companies listed on the Jakarta Stock Exchange. Data is collected using purposive sampling method. The ERC is estimated using pooled cross-sectional coefficient method (CRSM) and firm specific coefficient method (FSCM) in the observation period of 2001-2002. The result using CRSM and FSCM shows that audit committee firms ERC’s were bigger than non audit committee firm ERC’s. These result showed that unexpected earnings of audit committee firms were responssed stronger than non audit committee firm because investor believe that noise of audit committee firms earnings were less than non audit committee firms. The result indicate that investors belive audit committees have done their responssibility to monitor financial reporting process.
Keywords: audit committee, earnings responsse coefficient, pooled cross-sectional coefficient method, and firm specific coefficient method, earnings quality